Enhancing Storytelling Skills Through Andragogy-Based Training Programs for Kindergarten Teachers - Herdina Indrijati; Maulia Gitawati Indiswari (MOTIVA: JURNAL PSIKOLOGI, 2026)
Abstract :Teachers play a significant part in children's learning at kindergarten. It is imperative for teachers to be able to determine innovative teaching methods, one of which is storytelling. Through storytelling, teachers can deliver learning objectives in an effective and positive way. This is why a study was conducted on the effectiveness of storytelling training based on andragogy theory to develop storytelling skills among kindergarten teachers in Jember. Andragogy theory is a significant component of adult learning, as it employs methodologies tailored to the needs of adults. A total of 38 kindergarten teachers participated in this study. A quantitative quasi-experimental approach was used in the research. Pre-test and post-test measurements were obtained through a video task that was scored based on 24 indicators of storytelling competencies indicators. The collected data were then analysed using SPSS 25 for Windows, employing descriptive analysis and the Wilcoxon test for hypothesis testing. The mean score of participants in the pre-test was 13.87 (N=38; SD=5.832), and the mean score in the post-test was 18.45 (N=38; SD=4.518). Overall,The Wilcoxon signed-rank test demonstrated that the training effectively improved storytelling competencies in improving storytelling competencies among kindergarten teachers, with p < .001.